The Application of „Gedicht” Entitled Am See and Der Sommer As Learning Media for Reading Skills in German Language for Grade XII – 8 Students at SMAN 3 Lamongan - Hana, Alif Nur; Julaikah, Dwi Imroatu (LATERNE, 2025)
A Gedicht (poem) is a form of German literary work that is often utilized in language learning. Poetry has the potential to encourage students to think critically, improve their reasoning abilities, and enhance their imagination. Based on an interview conducted with the German teacher at SMAN 3 Lamongan on May 7, 2024, it was found that students’ low reading interest was due to the use of learning media that had not yet effectively supported the learning process. Therefore, this study aims to analyze the implementation of Gedicht as a learning medium to improve German reading skills among Grade XII–8 students of SMAN 3 Lamongan, as well as to identify their responses to its use.This research employed a descriptive quantitative method. Observation results showed that using Gedicht as a learning medium supported students’ reading skills, with observation scores increasing from 60% in the first session to 80% in the second session. The research instruments included observation sheets and post-activity questionnaires.Student responses to the use of Gedicht as a learning medium were also highly positive, with an average questionnaire score of 80.67%. Thus, it can be concluded that Gedicht is a viable alternative learning medium that can serve as a variation in German language instruction to enhance students’ reading skills. Keywords : Gedicht, Literary Work, Learning Medium, Student Response, German Language Learning.